Цифровой инвариантный стабилизатор танковой пушки - Александрова, Татьяна Евгеньевна; Александрова, И. Е.; Лазаренко, А. А. (НТУ "ХПИ", 2012)
Scheme of digital invariant tank gun stabilizer with high noise immunity with digital Butterwort and Lanczos filters is proposed
Keywords: автоколебания; рабочая жидкость; цифровые низкочастотные фильтры; гидроцилиндр